Slowly dispersing neotenic beetles can speciate on a penny coin and generate space-limited diversity in the tropical mountains - Bray, Timothy C; Bocak, Ladislav (Scientific reports, 2016)
We demonstrate the controversial origin of a biological species within an area of a few kilometres in the absence of physical barriers. We employed nuclear rRNA/mitochondrial and genome-wide SNP approaches to infer relationships of four species of net-winged beetles characterised by female neoteny. Three species are distributed at low elevations and a single population colonised a 40 km(2) highland plateau and established distinct biological species despite incomplete genetic isolation. The speciation process is extreme in the highly localised spatial scale, due to the low dispersal power of neotenics, and provides clear support for a microallopatric model based on ecological conditions. In contrast with neutral evolution in a homogenous environment, as demonstrated by the genetic divergence and morphological similarity of two widely distributed low-mountain species, the environmental characteristics of the high-mountain plateau led to the origin of a species adapted to the local mimetic pattern and characterised by morphologically distinct genitalia. We conclude that the low dispersal propensity promotes neutral genetic differentiation in the first stage, but environmental characteristics play an important role the final phase of the speciation process. The unexpected speciation at such an extreme geographic scale points to the in situ origin and uniqueness of the mountain fauna.
Keywords: Polymorphism, Single Nucleotide; druhová specificita; Phylogeny; Sequence Analysis, DNA; Ecosystem; jednonukleotidový polymorfismus; Biological Evolution; zvířata; Coleoptera; sekvenční analýza DNA; tropické klima; Male; fylogeneze; biologická evoluce; Species Specificity; brouci; Tropical Climate; Animals; mužské pohlaví; ekosystém